Jornalistas Em Direcaao As Instituicoes (1970-2010) (Global Journal of Human-Social Science, 2020)
By analyzing the conditions of production of the biographical and memorialistic records of the Brazilian journalistic elite that occurred between the dictatorial period and the years of redemocratization it was possible to enlighten structuring characteristics of the professional journalistic market, its hierarchical structure, internal conflicts, forms of legitimation and constitutive elements of professional identity. This paper presents part of an original research on the Brazilian journalistic elite. Through this investigation, it was possible to identify the spheres of activity and consecration of journalists -notably, the press, politics, literature and the universityand the transposition of journalists to the State, either as occupants of elective positions in the legislative power, or in the public servants career in statutory positions of public universities, a phenomenon that resulted in the increase of the production of memory and history in the scientific field. This process is personified here by the exemplary cases of
Keywords: journalistic elite; biographies and memoirs; sociology of elites; history of the press; sociology of culture